2008
DOI: 10.1104/pp.108.125435
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced DNA Damage Promotes Resistance to the Biotrophic Pathogen Hyaloperonospora parasitica in Arabidopsis

Abstract: Plant innate immunity to pathogenic microorganisms is activated in response to recognition of extracellular or intracellular pathogen molecules by transmembrane receptors or resistance proteins, respectively. The defense signaling pathways share components with those involved in plant responses to UV radiation, which can induce expression of plant genes important for pathogen resistance. Such intriguing links suggest that UV treatment might activate resistance to pathogens in normally susceptible host plants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 105 publications
3
39
1
Order By: Relevance
“…1). UV-B radiation has also been reported to increase plant resistance to microbial pathogens (Gunasekera et al, 1997;Wargent et al, 2006;Gunasekera and Paul, 2007;Kunz et al, 2008;Demkura and Ballaré, 2012) and can interact with the plant to modify the composition of microbial communities in the phyllosphere (Kadivar and Stapleton, 2003;Balint-Kurti et al, 2010). Treatment with unnaturally high doses of UV-B radiation, or with UV wavelengths not present in the daylight spectrum (UV-C, l , 280 nm), has also been reported to activate defense-related pathways in several species (Bridge and Klarman, 1973;Brederode et al, 1991;Conconi et al, 1996;Mert-Turk et al, 2003;Glawischnig, 2007); however, the ecological significance of these responses is not clear.…”
Section: Uv-b and Uvr8mentioning
confidence: 99%
“…1). UV-B radiation has also been reported to increase plant resistance to microbial pathogens (Gunasekera et al, 1997;Wargent et al, 2006;Gunasekera and Paul, 2007;Kunz et al, 2008;Demkura and Ballaré, 2012) and can interact with the plant to modify the composition of microbial communities in the phyllosphere (Kadivar and Stapleton, 2003;Balint-Kurti et al, 2010). Treatment with unnaturally high doses of UV-B radiation, or with UV wavelengths not present in the daylight spectrum (UV-C, l , 280 nm), has also been reported to activate defense-related pathways in several species (Bridge and Klarman, 1973;Brederode et al, 1991;Conconi et al, 1996;Mert-Turk et al, 2003;Glawischnig, 2007); however, the ecological significance of these responses is not clear.…”
Section: Uv-b and Uvr8mentioning
confidence: 99%
“…It is common knowledge that plants with certain mycorrhizal associations are less sensitive to cadmium stress than nonmycorrhizal plants (Schutzendubel and Polle, 2002). Several recent reports have shown that plants exposed to UV-C light acquire protection against pathogen infection (Kunz et al, 2006(Kunz et al, , 2008. Moreover, one of the reports proved that plants treated with salicylic acid exhibited higher tolerance to UV-B and UV-C light (Mahdavian et al, 2007).…”
Section: The Progeny Of Infected Plants Exhibit Higher Resistance Tomentioning
confidence: 99%
“…What is more, it has been proposed that the general response induced by UV treatment can be advantageous to resist to other environmental factors (e.g. biocides) (Kunz et al, 2008). However, there are only a few studies on higher plants that addressed the combined effects of enhanced UV-radiation with metals and nothing is known about the interactions of UV with NPs.…”
Section: Introductionmentioning
confidence: 99%